Investigation of preoperative physical activity level in kidney transplant recipients and its impact on early postoperative recovery: A retrospective cohort study - Li, Guo; Guo, Qi-fan; Zhao, Shang-ping; Wang, Miao-wei; Zhang, Xia; Wang, Ao; Gui, Chen-fan; Tan, Qi-ling; Gao, Qiang (Frontiers in Surgery, 2023)
Adequate physical activity (PA) level indicates to better exercise capacity and physical fitness. However, most of the evidence for PA level in the transplantation journey falls in the posttransplant phase. The aim of this retrospective study was to investigate the preoperative PA level in kidney transplant recipients (KTRs) and its impact on early postoperative recovery. 113 patients who received kidney transplantation at West China Hospital of Sichuan University were enrolled and allocated into the low PA level group (Group L, n = 55) and medium to high PA level group(Group MH, n = 58) according to PA level measured by the Chinese version of the International Physical Activity Questionnaire - Long. Moreover, data of these patients were reviewed and analyzed. The KTRs showed a lower PA level than the general population during preoperative phase, and KTRs in Group MH showed a better ambulatory function early after the operation compared to Group L. The time spent by patients to achieve transfer out of bed was associated with a better early ambulation distance and a short postoperative LOS. Even no more within-group differences in other early recovery indicators were observed, the preoperative PA level of KTRs shall be concerned by medical workers.